2021
DOI: 10.1111/iar.12396
|View full text |Cite
|
Sign up to set email alerts
|

Non‐metamorphosed autochthonous Kuncha‐Naudanda‐Heklang Formations and their differences from those of the Kuncha nappe: A multichronological approach

Abstract: Non-metamorphosed, autochthonous Lesser Himalayan sediments (LHS), which are correlated to the Kuncha and Naudanda Formations, were found in a narrow belt between the Main Boundary Thrust and the Lesser Himalayan Thrust at the base of the Kuncha nappe in southeastern Nepal. The autochthonous Naudanda Formation is comprised of cross-bedded and rippled orthoquartzite and yielded a maximum depositional age of 1795.1 Ma ±5.1 Ma using detrital zircons. Low-grade metamorphosed quartzite in the Kuncha nappe yielded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nakajima et al (2020aNakajima et al ( , 2020b deals with northward lateral cooling of Kathmandu and Kuncha nappe revealed by zircon fission-track (ZFT) dating. Distribution of nonmetamorphosed LHS along the southern margin of the Lesser Himalaya was confirmed by the zircon fission -track and Pb-Pb dating by Kobayashi et al (2021). Uplift and erosion history of the Himalaya was discussed on the basis of heavy mineral composition of sandstone of the Siwalik Group and sediment core of the Bengal Deep Sea Fan in Yoshida et al (2021).…”
mentioning
confidence: 85%
“…Nakajima et al (2020aNakajima et al ( , 2020b deals with northward lateral cooling of Kathmandu and Kuncha nappe revealed by zircon fission-track (ZFT) dating. Distribution of nonmetamorphosed LHS along the southern margin of the Lesser Himalaya was confirmed by the zircon fission -track and Pb-Pb dating by Kobayashi et al (2021). Uplift and erosion history of the Himalaya was discussed on the basis of heavy mineral composition of sandstone of the Siwalik Group and sediment core of the Bengal Deep Sea Fan in Yoshida et al (2021).…”
mentioning
confidence: 85%
“…The LHS distributed in eastern Nepal are divided into three geotectonic units; the Lesser Himalayan (LH) para‐autochthon, the Kuncha nappe, and the MCT zone. The LH para‐autochthon is composed of the Paleoproterozoic sediments of the Lower Nawakot Group (∼2,500 m thick: Kobayashi et al., 2021; Rai et al., 2016) and the Gondwana and post‐Gondwana foreland basin sediments of the Tansen Group (∼2,400 m thick: Sakai, 1983). The Kuncha nappe is separated from the LHS para‐autochthon by the Lesser Himalayan Thrust (known as the Ramgarh Thrust: Pearson & DeCelles, 2005) at its base.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The similar kind of study made by Baral et al (2022) has correlated the Sapt Kosi Formation with the Taltung Formation and the Tamrang Formation with the Dumri Formation of western Nepal. Kobayashi et al (2021) has correlated the Mulghat Formation and the Chiuribas Formation with the Kuncha Formation based on multichronological approach. The Sangure Quartzite has been correlated with the Naudanda Quartzite and the Raguwa Formation along with the Phalametar Quartzite has been correlated with the Heklang Formation (Sakai, 1985) of western Nepal.…”
Section: Introductionmentioning
confidence: 99%